In-door Climate Remediation Based on Multidisciplinary University Research Based Open Innovation - From innovation process to technical results. (2014) - Lonholdt, Jens Ronnow; Andersen, Birgitte; Jakobsen, Rasmus; Johansen, Carsten; Pedersen, Bettina; Prieme, Anders; Terkelsen, Mads; Karlby, Lone Tolstrup
No abstract available